Changes in growth characteristics and ginsenoside contents of wild-simulated ginseng with different harvest times in South Korea - Yeong-Bae Yun; Hae-Yun Kwon; Yurry Um (Applied Biological Chemistry, 2024)
Abstract Wild-simulated ginseng (WSG, Panax ginseng C.A. Meyer) is grown in mountainous forests, without the chemical treatment or installation of artificial facilities. This study aimed to investigate monthly changes in growth characteristics and ginsenoside contents in WSG to suggest the optimal harvest time. Four-year-old WSG were collected in the same area every month, and their growth characteristics and ginsenoside contents were measured. The growth characteristics of aerial and root parts were measured from May to July and from March to December, respectively. For the aerial part, most growth characteristics of WSG decreased over time, except for stem length. For the root part, rhizome length increased over time except for September, while the root diameter and weight of root part were mostly consistent. The root length increased by September, while the number of rootlets was the highest at May. At July, the total ginsenoside content of WSG was significantly the highest, while the total ginsenoside content at October was the lowest. This result was believed to be due to the F2, Rd, and Rg1 contents of the aerial part, rather than the root part. Also, based on these growths and the ginsenoside contents of WSG, the optimal harvest time for WSG is considered to be late spring–summer (May–July) when the aerial part can be identified.